If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(-2 + 9d) + 9d + d + -6 = 0 (-2 * 9 + 9d * 9) + 9d + d + -6 = 0 (-18 + 81d) + 9d + d + -6 = 0 Reorder the terms: -18 + -6 + 81d + 9d + d = 0 Combine like terms: -18 + -6 = -24 -24 + 81d + 9d + d = 0 Combine like terms: 81d + 9d = 90d -24 + 90d + d = 0 Combine like terms: 90d + d = 91d -24 + 91d = 0 Solving -24 + 91d = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 91d = 0 + 24 Combine like terms: -24 + 24 = 0 0 + 91d = 0 + 24 91d = 0 + 24 Combine like terms: 0 + 24 = 24 91d = 24 Divide each side by '91'. d = 0.2637362637 Simplifying d = 0.2637362637
| 8n+12-5n=21 | | 9x^2+3-80x-6=x-3 | | 8t+14=2(8t-5) | | 2x^2+4X=7 | | 2y+2x=4 | | 2x+14=32 | | 10UV+3UV-4uv= | | 9x^2+3-80x+6=x-3 | | 4x+10=66 | | 42=18-4x | | 7x-8=34 | | 10gh+7jk-8gh+2jk+4jk= | | 7n+5-9n=8-2n-3 | | 5x-6=59 | | 8-5x=-37 | | 9x-11=97 | | 7x+8=43 | | (x+1)(x+6)=2x | | (6x-7)(8x+5)=0 | | (6x+7)(7x-9)=0 | | 2x-15+x=90 | | 4x-5=43 | | 45ghf(9hg+6)-9ghf+14r= | | 3x^2+5x+1=0 | | 2(n-8)=-6 | | 2+6j= | | 27c+38cdg= | | 6d+5d-d-10d= | | 3BC-BC+10BC-7BC= | | 3x+9= | | 6qr+3q= | | 6x+3= |